2019
DOI: 10.1111/jop.12830
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Interleukin‐18 gene polymorphism and serum levels in oral lichen planus in an Indian population

Abstract: Background Oral lichen planus (OLP) is a chronic, inflammatory disease with uncertain etiology. The aim of this study was to assess Interleukin‐18 (IL‐18) gene polymorphism and serum levels in OLP cases of Indian origin and to compare them with a control population of similar background. Methods The assessment of single‐nucleotide polymorphisms (SNPs) of IL‐18 gene at promoter regions −137(G/C) and −607(C/A) was done in 70 OLP cases and 70 healthy controls using sequence‐specific primer‐polymerase chain reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
0
7
0
2
Order By: Relevance
“…IL‐12 and IL‐18 synergistically enhance IFN‐γ mRNA transcription by activating the transcription factors STAT4 and AP‐1, whilst inhibiting the synthesis of IL‐10, a Th2‐associated cytokine (Nakahira et al, 2002). In support of this, IL‐18 serum levels are elevated in OLP patients and an IL‐18 genetic polymorphism has been associated with OLP susceptibility (Negi et al, 2019), although more studies are needed to investigate the role of IL‐18 in regulating Th1 differentiation in OLP.…”
Section: Th1/th2 Paradigm and Other T‐cell Subsetsmentioning
confidence: 96%
“…IL‐12 and IL‐18 synergistically enhance IFN‐γ mRNA transcription by activating the transcription factors STAT4 and AP‐1, whilst inhibiting the synthesis of IL‐10, a Th2‐associated cytokine (Nakahira et al, 2002). In support of this, IL‐18 serum levels are elevated in OLP patients and an IL‐18 genetic polymorphism has been associated with OLP susceptibility (Negi et al, 2019), although more studies are needed to investigate the role of IL‐18 in regulating Th1 differentiation in OLP.…”
Section: Th1/th2 Paradigm and Other T‐cell Subsetsmentioning
confidence: 96%
“…In lichen planus a statistically significant higher mean serum level of IL-18 was found compared to healthy controls [33]. Moreover, it was observed that in a group of erosive lichen planus compared to nonerosive lichen planus an elevated level of IL-18 is present, but it is unclear whether these findings are statistically significant and could help to base the diagnosis the erosive subtype of lichen planus [33,34].…”
Section: Interleukinsmentioning
confidence: 99%
“…U chorych z liszajem płaskim odnotowano statystycznie znamienny wzrost średniego stężenia IL-18 w porównaniu z osobami zdrowymi z grupy kontrolnej [33]. Zaobserwowano ponadto, że w grupie pacjentów z postacią nadżerkową liszaja płaskiego (w porównaniu z postacią nienadżerkową) występuje podwyższone stężenie IL-18.…”
Section: Interleukinsunclassified
See 1 more Smart Citation
“…Raised cytokines: Several interleukins (IL) such as IL1, 2, 4, 5, 6, 8, 10, 12, 17, and 18 have been implicated in the causation and progression of oral lichen planus. [7] Genetic polymorphisms of IL-18 [31] , TNFα [32] , [33] , [34] , [35] , IFNγ [36] , [37] , [38] , IL-10 [33] , [35] , IL-17 [39] , IL-1ß [34] , IL-12 [40] , IL-8 [41] , IL-4 [37] have also been associated with OLP. Histopathologically, they damage the basement membrane and cause widespread tissue destruction leading to the formation of clinically observable lesions.…”
Section: Introduction/backgroundmentioning
confidence: 99%